1994
DOI: 10.1177/0310057x9402200419
|View full text |Cite
|
Sign up to set email alerts
|

Control of Carbon Dioxide Levels during Neuroanaesthesia: Current Practice and an Appraisal of our Reliance upon Capnography

Abstract: With the widespread availability of capnography, many anaesthetists have swung away from formally verifying hypocapnia by intraoperative arterial blood gas analysis and, instead, have come to rely upon capnography as an acceptable and constant predictor of arterial CO 2 tension (PaCOJJ during neurosurgery. However, the nature of the arterial-endtidal CO 2 gradient is complex, and is frequently unexpectedly large, or even negative. The importance of close intraoperative CO 2 control during neurosurgery-more spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…While a negligible gradient exists in health, it is an increase in alveolar deadspace in the hypovolaemic trauma patient that contributes to regional ventilation-perfusion mismatch and the observed Pa-etCO 2 gradient. The data from our study confirm earlier comments on the potential for PetCO 2 to be a misleading guide for adequacy of ventilation 6,13,14 . This is relevant as ventilation (via a self-inflating Laerdel TM or Ambu TM bag) in the prehospital setting is typically titrated to PetCO 2 and not with a ventilator with spirometry analysis.…”
Section: Discussionsupporting
confidence: 88%
“…While a negligible gradient exists in health, it is an increase in alveolar deadspace in the hypovolaemic trauma patient that contributes to regional ventilation-perfusion mismatch and the observed Pa-etCO 2 gradient. The data from our study confirm earlier comments on the potential for PetCO 2 to be a misleading guide for adequacy of ventilation 6,13,14 . This is relevant as ventilation (via a self-inflating Laerdel TM or Ambu TM bag) in the prehospital setting is typically titrated to PetCO 2 and not with a ventilator with spirometry analysis.…”
Section: Discussionsupporting
confidence: 88%
“…Alternatively, areas of low ventilation-perfusion ratios (shunt) result in ineffective gas exchange and the addition of blood with a high partial pressure of CO 2 to the arterial circulation contributing to the increased ET-CO 2 to PaCO 2 gradient. [ 17 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ), a potent cerebral vasodilator, is associated with CBF, which may contribute to ICP change [2,3]. It has been reported that the CBF can be affected dynamically, within a few minutes, in response to arterial carbon dioxide concentration (PaCO 2 ) change and tight control of PaCO 2 can be associated with neurological outcomes [4], as well as important to improve surgical outcomes even in non-neurosurgical patients [5,6]. Therefore, PaCO 2 should be deliberately monitored during mechanically ventilated patients, particularly in neurocritically-ill patients.…”
Section: Introductionmentioning
confidence: 99%